BIMification: How to create and use BIM for retrofitting. (October 2018) - Scherer, Raimar J.; Katranuschkov, Peter
Graphical abstract: Highlights: New method for generating and using BIM for energy retrofitting of old buildings. The proposed method comprises 3 interrelated tasks: Anamnesis, Diagnosis, Therapy. Templates help to fill in modeling gaps in the needed system identification cycle. A variation model enables the use of templates for retrofitting design variants. The developed framework can be reused in other domains such as bridge retrofitting. Abstract: Building Information Modeling (BIM) is rapidly advancing as an efficient new approach to cooperative building design and construction. However, BIM methodology is still mainly developed and applied for new building projects. The strong societal needs to improve the quality and the overall performance of the existing building stock, especially with regard to energy use, are yet insufficiently supported by BIM. In this paper we propose a structured approach towards the creation of a building information model of an existing building and its use for the purpose of retrofitting or renovation, based on the standard IFC specification (ISO 16739). It implies a process we define as BIMification . This process undergoes two major stages: (1) Anamnesis, dedicated to the survey and collection of facts about the building, and (2) Diagnosis, dedicated to the analysis and interpretation of the collected facts to obtain the necessary understanding of the building and its performance and prepare for the retrofitting design. The paper outlines the broader research aim that triggered the development of the suggested approach and presents the overall concept and methodology, the ICT platform under implementation and the current state of the work. Discussed are also the scope of the approach, envisaged perspectives and further development efforts.